"A Part of Who I Am": Material Objects as "Plot Devices" in the Formation of Religious Selves. Issue 1 (19th April 2017) - Winchester, Daniel
Abstract : What role do material objects play in the formation of religious subjects? Drawing from an ethnographic investigation of the evolving relationships between a group of Eastern Orthodox converts and their religious icons, this article develops a theoretical approach to this question that conceptualizes material artifacts as "plot devices" in the formation of religious identity narratives. Integrating insights from studies of material religious culture with narrative theories of identity, this article argues that religious artifacts become significant to religious identity construction to the extent they act as resources for the configuration of a narrative structure in which transcendent or sacred others play a part. As the empirical details of this study demonstrate, attending to how religious objects' symbolic meanings (i.e., who or what they represent) are mediated by their unique material characteristics (how they make meanings physically present to social actors in embodied social interaction) is of vital importance for explaining the significant role material artifacts play in the religious emplotment of action and experience.